An In-vitro Evaluation of the Ability of 5.25% NaOCl in the Elimination of Enterococcus Faecalis from Root Canal - MS. Sheykhrezaei; M. Aligholi; KH. Biglar (Tehran University of Medical Sciences, 2004)
Statement of Problem: Sodium hypochlorite (NaOCl) have been widely used as an irrigant since it has been introduced to endodontics by walker in 1936, because of its bleaching, deodorizing and tissue dissolving properties. It should be used clinically in concentrations of 3% to 5%. Purpose: The aim of this study was to evaluate the effectiveness of the NaOCl to eliminate Enterococcus faecalis (E.f) from root canals in comparison with Normal saline. Materials and Methods: In an interventional study forty freshly extracted single canal human teeth were chosen. They were sectioned at the CEJ, instrumented and Sterilized. Then they were contaminated with E.f solution and incubated. These samples divided into two groups randomly. Root canals were irrigated and filled with 5.25% NaOCl for five minutes in group one, and with normal saline in group two. Then samples were obtained from canals with sterile paper points and cultured for four days. The appearance of turbidity in cultured solutions was the indication to of E.F presence. In order to confirm the specific presence of E.F, three complementary microbiologic tests were applied. Results: All cultures obtained from NaOCl group were negative and all of normal saline group were positive. Conclusion: these results indicate the ability of 5.25% NaOCl to eliminate E.F in prepared root canals with wide diameter.